Hematological indices - a new marker of inflammation in old patients and centenarians with trophic ulcers of lower extremities - Svetlana V. Topolyanskaya; Leonid I. Bubman; Viktor V. Karpov; Aleksei I. Nechaev; Stanislav O. Khan; Mariia A. Korshunova; Georgii G. Melkonyan; Svetlana A. Ratchina; Leonid I. Dvoretsky (LLC "MEDIAFORMAT", 2023)
Aim. To study the significance of various hematological indices as markers of laboratory inflammatory activity in patients with trophic ulcers of the lower extremities and compare them with similar indices in old patients with coronary artery disease (CAD). Materials and methods. The study enrolled 256 patients; 166 patients with trophic ulcers - in the main group, 90 with CAD, but without ul-cers - in the comparison group. The main group consisted of 31.9% men and 68.1% women. The mean age of patients with trophic ulcers reached 80.8±10.1 years (from 61 to 101 years); 30.1% of patients were centenarians. The ratio of the number of neutrophils to lymphocytes (NLR), neu-trophils to monocytes (NMR), platelets to lymphocytes (PLR), lymphocytes to monocytes (LMR) and systemic immune-inflammation index (SII -platelet count хNLR) were determined. Results. The mean count of leukocytes in patients with trophic ulcers was 7.1±2.6×109/l, neutrophils - 4.7±2.3×109/l, lymphocytes -1.8±2.2×109/l, monocytes - 0.6±0.3×109/l, platelets - 278.5±110×109/l. The mean values of NLR in the group of patients with ulcers reached 3.6, NMR - 15.4, PLR - 214.1, LMR - 5.9, SII - 1102.3. In patients with trophic ulcers, the count of leukocytes (6.7×109/l and 5.9×109/l; p=0.002), neutrophils (4.2×109/l and 3.7×109/l; р=0.002) and platelets (252×109/l and 205×109/л; p<0.0001) was significantly higher than in the group of patients with CAD. NLR (2.7 and 2.1; p=0.003) and PLR (172 and 133; p<0.0001) in patients with trophic ulcers of the lower extremities was higher, but LMR was lower (2.8 and 3.1; p=0.01), than in patients with CAD. In the group of patients with trophic ulcers, the median of the SII reached 452, while in patients with CAD it was 296 (p=0.00003). The median of erythrocyte sedimentation rate in patients with the lower ex-tremities ulcers was 32 mm/h, in patients with CAD - 21 mm/h (p=0.00002).A direct relationship was registered between interleukin-6 level and leukocytes (r=0.32; p=0.01), neutrophils (r=0.36; p=0.005), platelets (r=0.36; p=0.006), NLR (r=0.30; p=0.02), PLR (r=0.27; p=0.03) and SII (r=0.31; p=0.01). Conclusions. The study results suggest that various hematological indices can be used as markers of laboratory inflammatory activity in patients with trophic ulcers of the lower extremities in the old age and centenarians.